Contextualization of Jihad Verses in the Qur'an: A Thematic Study and Its Implications for National Education - KM, Ghozy; Ghozali, Abdul Malik; Badi'ah, Siti (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2025)
This article aims to explore the contextual meaning of jihad verses in the Qur'an and analyze their relevance to national education values. By using a thematic interpretation (tafsir maudhū‘ī) approach, the study focuses on verses that are often misunderstood, such as QS. Al-Baqarah [2]: 190 and QS. At-Taubah [9]: 5. Through this method, the research highlights that jihad in the Qur'an is not limited to physical warfare but embraces broader values such as self-discipline, social contribution, and the pursuit of justice. The study also critically discusses the implications of understanding these verses in relation to the development of character education and religious moderation in Indonesia. The findings show that a contextual reading of jihad verses can significantly contribute to shaping a tolerant, democratic, and peace-oriented national identity. This article offers an academic contribution in bridging Islamic textualism with the civic values of the modern nation-state.